Effectiveness of Special Breathing Exercises on Increasing 60-Meter Running Speed for 5th Grade Students of SDN 37 Krui, Ngaras District, Pesisir Barat Regency - Sukmana, Fajar; Muhtar, Tatang; Supriyadi, Tedi (Indonesian Journal of Sport Management, 2025)
This study aims to determine the effectiveness of special breathing exercises in improving the 60-meter running speed of 5th grade students at SDN 37 Krui, Ngaras District, Pesisir Barat Regency. Using a pre-experimental one-group pretest–posttest design, a group of students received structured breathing exercises for a set period. Data were collected through 60-meter sprint tests administered before and after the intervention. The results showed a significant improvement in running speed, indicating that special breathing exercises effectively enhance short-distance sprint performance in elementary school students. This finding highlights the importance of integrating proper breathing techniques into physical education programs to support students’ physical fitness and athletic development.